2017
DOI: 10.1016/s0140-6736(17)30638-4
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of early tranexamic acid administration on mortality, hysterectomy, and other morbidities in women with post-partum haemorrhage (WOMAN): an international, randomised, double-blind, placebo-controlled trial

Abstract: SummaryBackgroundPost-partum haemorrhage is the leading cause of maternal death worldwide. Early administration of tranexamic acid reduces deaths due to bleeding in trauma patients. We aimed to assess the effects of early administration of tranexamic acid on death, hysterectomy, and other relevant outcomes in women with post-partum haemorrhage.MethodsIn this randomised, double-blind, placebo-controlled trial, we recruited women aged 16 years and older with a clinical diagnosis of post-partum haemorrhage after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
404
3
13

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 1,084 publications
(440 citation statements)
references
References 20 publications
3
404
3
13
Order By: Relevance
“…24 WOMAN trial, as discussed above, did not show that the use of TXA had any effect on the incidence of thromboembolic events, organ failure, sepsis or seizure in the more than 20 000 patients studied. 29 It should be noted that TXA crosses the placenta. However, after an intravenous injection of 10 mg/kg in the mother, the concentration only rises to a maximum of 31 μg/mL of foetal serum.…”
Section: Data Analysesmentioning
confidence: 99%
“…24 WOMAN trial, as discussed above, did not show that the use of TXA had any effect on the incidence of thromboembolic events, organ failure, sepsis or seizure in the more than 20 000 patients studied. 29 It should be noted that TXA crosses the placenta. However, after an intravenous injection of 10 mg/kg in the mother, the concentration only rises to a maximum of 31 μg/mL of foetal serum.…”
Section: Data Analysesmentioning
confidence: 99%
“…However, recently, a new randomised, double-blind, placebo-controlled trial was published, concluding that tranexamic acid reduces PPH death of clinically diagnosed women and that early treatment seems to optimise benefits. 109 limitations The proxy indicators are probably more suitable to evaluate maternal and neonatal eHealth programmes or components of a programme. For specific maternal/ neonatal eHealth programmes or projects (eg, targeted at HIV infected mothers), additional indicators might be identifiable (eg, vertical transmission of HIV/AIDS).…”
Section: Discussionmentioning
confidence: 99%
“…However, whilst the trial was underway, new research suggested a shorter therapeutic window than 8 hours 12, 13 . The new data showed that tranexamic acid is most likely to improve outcome if given soon after injury and would be unlikely to improve outcome if given beyond three hours of injury.…”
Section: Trial Methodsmentioning
confidence: 99%
“…In 2011, the CRASH-2 trial showed that administration of tranexamic acid to poly-trauma patients within three hours of injury reduces deaths due to bleeding by about one third 11, 12 . In 2017, the WOMAN trial showed that administration of tranexamic acid to women with post-partum haemorrhage within three hours of delivery reduces deaths due to bleeding by about one third 13 . Later in 2017, results from an individual patient-level data meta-analysis of randomised trials of tranexamic acid in acute severe bleeding showed that whilst immediate treatment substantially improves survival, the survival benefit decreases by around 10% for every 15 min of treatment delay until 3 h, after which there was no benefit 14 .…”
Section: Introductionmentioning
confidence: 99%